Empowering multilingualism in children with autism: Insights from parents and EFL teachers - Mohamed, Amr; Shaaban, Tahany; Alazhar Jmaiel, Hassen (Specijalna edukacija i rehabilitacija, 2024)
Introduction. In today’s globalized world, the ability to use and understand more than one language, known as multilingualism, has become increasingly prevalent. Studies have demonstrated that children raised in multilingual environments can gain cognitive advantages, including improved problem-solving abilities, creativity, and cognitive f lexibility. Objectives. This study aimed to explore the methods used by parents and teachers when teaching English as a Foreign language (EFL) to children with autism spectrum disorder (ASD), as well as the difficulties they face in this endeavor. Methods. The research methodology involved conducting interviews with a total of 14 participants, including parents and teachers of children with ASD. Results. The study showed that incorporating visual aids, repetition, and modeling into EFL instruction had positive outcomes for children with ASD. These strategies resulted in enhanced social skills and language abilities. Teachers faced challenges in creating effective teaching methods for children with ASD, yet they also recognized the impressive ability of these children to learn new languages. In addition, the study highlighted the significance of parents and teachers working together to create language learning programs that are effective for children with ASD. Conclusion. Additional research is necessary to develop a more comprehensive understanding of the difficulties that teachers encounter when instructing children with ASD in EFL. In order to further advance our understanding, it would be beneficial for future research to concentrate on developing and assessing inclusive language learning programs that cater to the specific requirements of children with ASD.
Keywords: multilingualism; autism spectrum disorder; perspectives; English as a foreign language; qualitative research